2004
DOI: 10.1111/j.1460-9568.2004.03207.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose γ‐irradiation promotes survival of injured neurons in the central nervous system via homeostasis‐driven proliferation of T cells

Abstract: Protective autoimmunity was only recently recognized as a mechanism for attenuating the progression of neurodegeneration. Using a rat model of optic nerve crush or contusive spinal cord injury, and a mouse model of neurodegenerative conditions caused by injection of a toxic dose of intraocular glutamate, we show that a single low dose of whole-body or lymphoid-organ gamma-irradiation significantly improved the spontaneous recovery. Animals with severe immune deficiency or deprived of mature T cells were unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
0
46
2
Order By: Relevance
“…Because the effects are often small, difficult to reproduce, and nonamenable to mechanistic study, past studies of radiation-induced effects have often been controversial (21,22). Of most relevance to our findings, a recent paper reported protective effects of low-dose radiation for RGCs damaged by mechanical crush or NMDA toxicity (23). Although interesting, the results were of modest effect.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Because the effects are often small, difficult to reproduce, and nonamenable to mechanistic study, past studies of radiation-induced effects have often been controversial (21,22). Of most relevance to our findings, a recent paper reported protective effects of low-dose radiation for RGCs damaged by mechanical crush or NMDA toxicity (23). Although interesting, the results were of modest effect.…”
Section: Discussioncontrasting
confidence: 53%
“…For example, one of the largest results (from an optic nerve crush experiment performed on Lewis rats) resulted in a change of RGC survival from 40.3 Ϯ 1.8 to 114.4 Ϯ 5.6 RGCs per mm 2 . As estimated by Kipnis et al (23), this correlates to a rescue of Ϸ3,500 RGCs in We have obtained complete protection in the majority of animals in three independent experiments that were spaced in time.…”
Section: Discussionmentioning
confidence: 64%
“…Using this novel model, we found that, after challenge with 3-NP, none of the WT3 WT mice displayed any striatal lesions, whereas 60% of the surviving KO3 WT mice showed obvious bilateral striatal damage. Although similar exacerbation was not noted at the neurological behavioral level in KO3 WT mice, this discrepancy may be attributable to the overall smaller striatal damage in the KO3 WT groups, which is likely attributable to an immunosuppressive effect, as suggested in a previous study showing protection against spinal cord injury by BMT (Kipnis et al, 2004). Nonetheless, this result suggests that A 2A Rs on BMDCs are critical to the modulation of 3-NP-induced striatal damage observed in gKO mice.…”
Section: Different 3-np Intoxication Outcomes Incontrasting
confidence: 51%
“…Recent studies in our laboratory have shown that depletion of Treg in BALB͞c͞OLA mice significantly improves neuronal survival after mechanical injury of the optic nerve (6,45,46), presumably because it allows more efficient activation of Teff. However, neuronal survival can also be significantly improved by myelin antigens administered mucosally (11,12), via a mechanism that was suggested to be IL-10 dependent (12).…”
Section: Discussionmentioning
confidence: 99%